Risk Factors and Occurrences of Shigella spp in Ready-To-Eat Vegetable Salads (Ayamutsa) Sold in Gombe Metropolis - Abdullahi Tawfiq, Umar; Muhammad Mofio, Bintu; Babandi, Nura; Ibrahim Isiaka, Hussein; Rabi’u RA, Ummu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Shigella spp are pathogenic bacteria that cause shigellosis which is an ailment noted for significant disease burden especially in Africa. These bacteria are transmitted via contaminated food/water. In Gombe, ayamutsa is believed to pose health risks due to improper preparation and handling. Therefore, this research was aimed at investigating these ayamutsa for possible Shigella spp occurrence and also to identify risk factors responsible for the occurrence. 100 samples were inoculated on nutrient agar and SS agar. Identification was done using Gram’s staining and biochemical tests. Antibiotic sensitivity tests were conducted based on CLSI guidelines, and a questionnaire was used to obtain data for determining the association between handling practices and contamination. Results revealed 10% of samples were contaminated with Shigella spp. The sensitivity test showed the isolates were sensitive to gentamicin, Augmentin, ceftriaxone, but resistant to ofloxacin and oxacillin. Questionnaire analyses revealed there is significant association between contamination and some handling practices. The findings from this study revealed that ayamutsa contamination with Shigella spp in Gombe metropolis poses a threat to public health and could also serve as a persistent source of Shigella spp spread in the community which could lead to an outbreak of shigellosis.